Evaluation of degradation products and kinetics of poly(3-hydroxybytyrate-co-3-hydroxyhexanoate) superheated steam hydrolysis for the production of biocompatible oligoesters - Rajaratanam, Dhurga Devi (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
In order to apply polyhydroxyalkanoate (PHA) as various biomedical materials, controlled hydrolysis of PHAs was conducted using superheated steam (SHS) for the production of oligoesters. Changes in mass and molecular weight of poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) were monitored during the SHS treatment in a range of 130-190 °C. Produced oligoesters were analyzed using 1H and 13C-NMR to determine the chemical structures. Obtained kinetic parameters of degradation and chemical structures of oligoesters revealed that the SHS hydrolysis of PHBHHx preferentially proceeded at HHx*HB sequence and specifically occurred according to the SHS treatment temperatures, resulting in the formation of crotonyl-chain end at temperatures above 170°C.